A physically-based Human Skin Reflection Model - Li, Ling; Ng, C. (Wseas press, 2009)
A theoretical reflection model for human skin is presented. A layer of sebum has been included in the three-layer skin reflection model, since it is found over most parts of the body and contributes significantly to the specularity of human skin appearance. The Monte Carlo method is used to simulate the propagation of light in skin tissues. Optical and geometric properties are used as control parameters to influence the surface reflection and subsurface scattering of light within the sebum-covered skin layers. The bi-directional reflectance distribution function (BRDF) obtained from the simulation is used to render the appearance of human skin. Comparisons between the simulated BRDF results and experimental measurements show that the physical simulation is highly realistic.A theoretical reflection model for human skin is presented. A layer of sebum has been included in the three-layer skin reflection model, since it is found over most parts of the body and contributes significantly to the specularity of human skin appearance. The Monte Carlo method is used to simulate the propagation of light in skin tissues. Optical and geometric properties are used as control parameters to influence the surface reflection and subsurface scattering of light within the sebum-covered skin layers. The bi-directional reflectance distribution function (BRDF) obtained from the simulation is used to render the appearance of human skin. Comparisons between the simulated BRDF results and experimental measurements show that the physical simulation is highly realistic.